The effect of consuming milk and related products during human pregnancy over birth weight and perinatal outcomes: A systematic review and meta-analysis. (August 2020) - Pérez-Roncero, Gonzalo R.; López-Baena, María T.; Chedraui, Peter; Pérez-López, Faustino R.
Highlights: Meta-analysis regarding the effect of milk and related products (M&RPs) on fetal growth. There is a positive association between consuming a higher amount of M&RPs and birth weight. There is a positive effect of consuming higher amounts of M&RPs and infant length. Higher M&RP consumption was associated with reduced risks for small-for-gestational-age and low birth weight infants. Abstract: Objective: Data addressing the effect of milk and related products (M&RPs) on fetal growth are contradictory. The aim was to meta-analyze the effect of consuming M&RPs during human pregnancy over perinatal outcomes. Method: A systematic literature search was performed in PubMed, EMBASE, Scopus, Web of Science, and Cochrane Library. Eligibility criteria for selection were: studies evaluating the effect of consuming M&RPs during pregnancy over birth weight and different perinatal outcomes. Random effect models were used for meta-analyses, and effects are reported as mean differences (MD) or odds ratio (OR) and their 95 % confidence intervals (CIs). Results: Fourteen studies (111, 184 pregnant women) reported on the targeted perinatal outcomes. The meta-analysis of ten studies revealed a positive association between consuming a higher amount of M&RPs and birth weight (MD =51.0 g, 95 % CI 24.7–77.3), whereas in five studies a positive effect was observed on infant length (MD =0.33 cm, 95 % CI: 0.03−0.64). The higher birth weight was detected both in Western world gravids, consuming standard/conventional diets, as well as in vegetarian women from India. There were no significant differences in ultrasound measured fetal head circumference, biparietal diameter, abdominal circumference and femur length. The consumption of a higher amount of M&RPs was associated with a reduced risk of small-for-gestational age (SGA) (OR = 0.69, 95 % CI: 0.56−0.84) and low birth weight infants (OR = 0.63, 95 % CI: 0.48−0.84); in addition to a higher risk of large-for-gestational age (LGA) infants (OR = 1.11, 95 % CI: 1.02–1.21). Conclusion: The consumption of a higher amount of M&RPs during pregnancy was associated with greater infant birth weight and length; in addition to a lower risk of having SGA and low birth weight infants, and a higher risk of LGA infants.